PENINGKATAN KETRAMPILAN DAN MANAJEMEN KERAJINAN TEDUNG SEBAGAI INDUSTRI KREATIF LOKAL - Seminari, N.K.; Purnawati, N.K.; Rastini, N.M.; Kusumadewi, N.M.W. (Buletin Udayana Mengabdi; Vol 24 No 4 (2025): Buletin Udayana Mengabdi, 2025)
Village potential development has received significant attention as one of the targets in improving the village economy. There is a great need for community involvement in advancing the village economy. One of the creativity of the Mengwi Village community that has great potential is the making of tedung. Tedung craftsmen in this area have a long tradition; however, the model, shape, and method of use are not yet practical enough to meet community preferences. Most of the tedung work is done in their respective homes, with the final assembly process carried out in certain centers. The conditions of the workplace are still inadequate, recording is still done traditionally so that it produces unclear documentation, and understanding of customer service is still limited. The purpose of this community service activity is to develop more innovative tedung making skills while maintaining existing standards and improving business management. Community service was carried out in Mengwi Village, Badung Regency, by visiting homes and tedung production centers. The methods used were lectures and demonstrations. The results of the community service activities showed that entrepreneurs were able to produce more innovative products with more attractive models and had improved management practices in the fields of finance, marketing, and business ethics. In addition, the results of this community service are expected to improve comfort and health in the workplace. This service has the potential to increase the skills, knowledge and income of tedung craftsmen. Keywords: skills, management, creative industry, local.